AN IMPACT OF ASSESSING QUALITY ASSURANCE, GOVERNANCE AND MANAGEMENT ON HIGHER EDUCATION (An Applied Study of Kingdom of Bahrain) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The governance of Higher Education Institutions (HEIs) is a determining factor for the functioning andquality of higher education systems. Several the major challenges facing higher education are related to thequality assurance, governance, and management of HEIs specifically the PHEIs. With the increasingdemand for higher education as well as the acknowledgement of its role in promoting economic growth, itbecomes more essential to ensure that HEIs are managed in an effective manner. Based on the HigherEducation Review Unit (HERU)/National Authority for Qualifications & Quality Assurance of Education &Training (NAQQAET) review findings, a number of the major challenges facing higher education in theKingdom of Bahrain are related to the quality assurance, governance, and management of HEIs. Most HEIsface challenges in forming their governance structures and activities to be in line with international goodpractice. In many PHEIs there is a disjuncture between the institution’s vision and mission and its educationprovision. In addition, there is a blurring between ownership and governance in almost all PHEIs.Furthermore, governance and management structures are generally not clearly outlined, which means thatthere is a lack of good corporate governance. The researchers identify the factors affecting governance,management, and quality assurance of higher education from stakeholders’ perspectives.